2004
DOI: 10.1056/nejmoa040135
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Hyperkalemia after Publication of the Randomized Aldactone Evaluation Study

Abstract: The publication of RALES was associated with abrupt increases in the rate of prescriptions for spironolactone and in hyperkalemia-associated morbidity and mortality. Closer laboratory monitoring and more judicious use of spironolactone may reduce the occurrence of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
819
4
59

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,565 publications
(899 citation statements)
references
References 25 publications
17
819
4
59
Order By: Relevance
“…Risks of hyperkalemia and worsening renal function often limit use of MRA therapy in patients with heart failure 12, 13, 14. Several factors increase hyperkalemia risk, including renal insufficiency and diabetes mellitus 15, 16, 17, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…Risks of hyperkalemia and worsening renal function often limit use of MRA therapy in patients with heart failure 12, 13, 14. Several factors increase hyperkalemia risk, including renal insufficiency and diabetes mellitus 15, 16, 17, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an increase of in‐hospital death among HF patients was described also by Juurlink's group in a Canadian population study. In that population, the publication of RALES was associated with an increase in spironolactone use and in the rates of hospital admission for HK and subsequent in‐hospital death among HF patients 10. Similarly, another population study showed that spironolactone use was not associated with improved long‐term survival in the general HF population 15.…”
Section: Discussionmentioning
confidence: 97%
“…Demographic and mortality data were obtained from the Ontario Health Insurance Plan Registered Persons Database, a registry of all Ontario residents with publically‐funded health insurance, and physicians’ services were identified using OHIP physician claims data. These databases were linked in an anonymous fashion using encrypted Ontario health card numbers, and are routinely used to study drug safety 27, 28, 29, 30, 31, 32.…”
Section: Methodsmentioning
confidence: 99%